Smartphone-Based Cardiac Rehabilitation Program Improves Functional Capacity in Coronary Heart Disease Patients: A Systematic Review and Meta-Analysis - Bambang Dwiputra; Anwar Santoso; Budhi Setianto Purwowiyoto; Basuni Radi; Ade Meidian Ambari; Dwita Rian Desandri; Serlie Fatrin; Bashar Adi Wahyu Pandhita (Ubiquity Press, 2023)
Cardiac rehabilitation (CR) reduces mortality and morbidity in coronary heart disease (CHD); however, patients show a lack of adherence to CR. Alternatively, telehealth interventions have shown promising results for improving target outcomes in CR. This study aimed to review the effect of smartphone-based CR on the functional capacity of CHD patients. A literature search was performed using PubMed, MEDLINE, Embase, and Cochrane Library on 21 March, 2022 to find randomised controlled trials on smartphone usage in CR to improve functional capacity. Outcomes included maximal oxygen consumption (VO2 max), a 6-min walk test (6-MWT), quality of life, smoking cessation, and modifiable risk factors. Eleven trials recruiting CHD patients were reviewed. Wearable devices connected to smartphone- or chat-based applications were commonly used for CR delivery. Most trials managed to provide exercise prescriptions, education on medication adherence and controlling risk factors, and psychosocial counselling through the intervention. Functional capacity improved significantly following smartphone-based CR in CHD patients compared to control groups, as measured by VO2 max and 6-MWT; patients were more likely to quit smoking. Compared to traditional care, smartphones that delivered CR to CHD patients demonstrate superior outcomes regarding increasing functional capacity. There is no significant improvement on lipid profile, blood pressure, HbA1C, body mass index, and quality of life. It can be used either alone or as an adjunct. Ultimately, the patients' preferences and circumstances should be considered.